The Effects Of Genre Approach On Orang Asli’S Efl Descriptive Writing: A Case Study Of A Secondary School In Pahang - Phan, Jonathan Kar Jun (2022)
The indigenous Orang Asli in Malaysia who do not use English on a daily basis consequently have low English proficiency and poor writing skills. Their existing English as a foreign language (EFL) situation coupled with the ongoing problems in gaining access to proper education further stifles their English language development. In accordance with the long-term goals set by the Malaysian Education Blueprint 2015-2025 (MEB) and the fourth sustainable development goal of providing inclusive and equitable quality education to the indigenous community, this study assesses the effectiveness of the genre approach in improving secondary EFL Orang Asli students’ descriptive writing, and discovers their perceptions in using the genre approach as a framework to overcome challenges in learning descriptive writing. The conceptual framework encompasses Systemic Functional Linguistics (SFL), the teaching and learning cycle for genre writing, and the concept of scaffolding from the Sociocultural Theory of Cognitive Development.